FAKTOR SUKSES IMPLEMENTASI E-GOVERNMENT DI KABUPATEN TEGAL - Tania Aji Asri; Andri Widianto (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2019)
The development of the digital age quickly and technological progress information and communication changed the way interaction in the government and society with of elimination bulkhead bureaucratic organization and forming a network management system in a new phenomenon called E-government. E-government is a means of the organizers government based electronic. The purpose of this study was to anlyze the factors success supporting the implementation E-government as well as describe a picture of success implementation E-government in the regional financial and asset management agency (BPKAD) of tegal district. The collection of technique used data was observations, the interview, and technique inquiries based the questionnaire. Analysis technique used data was a quantitative analysis the descriptive using the scale likert’s and technique count the average weighted tool. The calculations with average weighted tool show that 55 factors succesful who asked the goal has got predicate good enough, with 37 factors in critical succes factor succesfull and 18 factors succesfull the final because the value of the average (mean) after calculated show value less than the 4. So that pulled the conclusion that 67,27 % of the study factors succesfull implementation E-government is said to be succesfull and 32,73% factos said factors succesfull not the final need to the evaluation to the fore for the realization of Good Corporate Governance